CONSTRAINTS IN FISH FARMING PRACTICES IN UTTAR PRADESH, INDIA-AN ANALYSIS - Dewan, Ritu; Pandey, S. K. (Journal of Indian Fisheries Association, 2015)
Aquaculture can be considered as a rapidly growing sector in many Indian states including Uttar Pradesh. The impressive overall upward trendÂ· in fish production is likely to continue in future years as there are plenty ofunutilized or underutilized fishery resources in the state. In spite of the growing popularity of aquaculture in the state, fish farmers have been experiencing financial, social and technical constraints in fish farming practic s. These constraints are adversely affecting farmers in obtaining expected fish yields and income. In this study, the most common problem areas were identified, analysed and ranked on the basis of farmers’ perception. Keywords: Fish farming, constraints, ranking, credit, seed, input price, subsidy, knowledge